A New Current Collector System for Lithium-ion Batteries - Badreldin Abdelhamid, Hossam Mohamed Nabil Mohamed (My University, 2025)
The study of rechargeable batteries has become increasingly important due to the growing demand for efficient energy storage in electronic devices, electric vehicles, and renewable energy systems. Within these batteries, current collectors act as conductive bridges between the external circuit and the active electrode materials, directly influencing the battery’s performance, weight, and cost. Traditional anode current collectors are typically made of thin copper foil due to its excellent electrical conductivity and mechanical properties. However, aluminium— commonly used as a cathode current collector—can be coated with a thin copper layer to create a composite material that offers comparable electrical conductivity while reducing both weight and material costs. In this thesis, such a composite foil, produced by coating a thin copper layer on aluminium foil, was investigated for its application in batteries as anode current collector and compared to commercial copper foil. The mechanical analysis revealed strong adhesion between the copper coating and the aluminium substrate, along with significantly improved adhesion of the electrode material to the collector compared to that of pure copper foil. Battery cycling performance was also evaluated. While the composite demonstrated acceptable short-term cycling behaviour, its performance was ultimately limited by defects in the copper layer. These defects led to undesirable side reactions between the exposed aluminium and lithium within the cell. With further optimization to eliminate these defects, the copper-coated aluminium composite has the potential to be a cost-effective and lightweight alternative to traditional copper current collectors—offering increased energy density without compromising battery capacity